Q: From the product of 12 and 9 subtract 13?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

9 x 3 = 27 9 + 3 = 12

The answer is 15 because the pattern is subtract one, add two

M=4, Just subtract 9 from 13 to get m's value.

To subtract a negative number, you must change the subtraction sign to an addition sign, then make the second number its opposite. Ex. (-9)-(-13) (-9)+(+13)=4

The sequence goes (starting from the six): Up 3: 6 + 3 = 9 Then you subtract 1: 9 - 1 = 8 Then you add 3 again: 8 + 3 = 11 then subtract 1 again: 11 - 1 = 10 The sequence is up 3, minus 1. You subtract 1 from 13 to get the 12, then you have to add 3 again. 12 + 3 = 15 15 comes next. Hope I helped! - Darg

Related questions

9 x 3 = 27 9 + 3 = 12

The answer is 15 because the pattern is subtract one, add two

-3

15x+12 = 6x + 13 Solve for x. Step 1. Get all the x's on the same side. Subtract 6x from each side: 15x-6x+12 = 6x-6x + 13 Step 2. Get x by itself, pt. 1. Subtract 12 from each side. 9x + 12-12 = 13-12 Step 3. Get x by itself pt.2. Divide each side by 9. 9x/9 = 1/9 x = 1/9

-3

You first multiply 6 by 13 giving you 78. Then subtract 9 giving you 69. Then subtract 6*6 which is 36 giving you 33. Then you subtract 9 to get 24.

M=4, Just subtract 9 from 13 to get m's value.

9

To subtract a negative number, you must change the subtraction sign to an addition sign, then make the second number its opposite. Ex. (-9)-(-13) (-9)+(+13)=4

The sequence goes (starting from the six): Up 3: 6 + 3 = 9 Then you subtract 1: 9 - 1 = 8 Then you add 3 again: 8 + 3 = 11 then subtract 1 again: 11 - 1 = 10 The sequence is up 3, minus 1. You subtract 1 from 13 to get the 12, then you have to add 3 again. 12 + 3 = 15 15 comes next. Hope I helped! - Darg

9/12 - 8/12 = 1/12

4x - 9 = 7x + 12 Subtract 4x from both sides: -9 = 3x + 12 Subtract 12 from both sides: -21 = 3x Divide both sides by 3: x = -7